2021
DOI: 10.2337/db21-0100
|View full text |Cite
|
Sign up to set email alerts
|

Increased Energy Expenditure and Protection From Diet-Induced Obesity in Mice Lacking the cGMP-Specific Phosphodiesterase PDE9

Abstract: Cyclic nucleotides cAMP and cGMP are important second messengers for the regulation of adaptive thermogenesis. Their levels are controlled not only by their synthesis, but also their degradation. Since pharmacological inhibitors of cGMP-specific phosphodiesterase 9 (PDE9) can increase cGMP-dependent protein kinase signaling and uncoupling protein 1 expression in adipocytes, we sought to elucidate the role of PDE9 on energy balance and glucose homeostasis in vivo. Mice with targeted disruption of the PDE9 gene,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…A more recent study showed that overexpression of PDE4D in the liver led to the development of NAFLD and hypertension in mice, which was attenuated by PDE4 inhibitor treatment [60]. Beyond PDE4, recent papers have shown a role of PDE9 and 10 in liver and lung fibrosis as well as diet-induced obesity [61][62][63][64]. Our data show a significant upregulation of PDE9A and 10A in the livers of AH patients (Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…A more recent study showed that overexpression of PDE4D in the liver led to the development of NAFLD and hypertension in mice, which was attenuated by PDE4 inhibitor treatment [60]. Beyond PDE4, recent papers have shown a role of PDE9 and 10 in liver and lung fibrosis as well as diet-induced obesity [61][62][63][64]. Our data show a significant upregulation of PDE9A and 10A in the livers of AH patients (Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…On day 5, iBAT and iWAT were dissected and immediately placed in Trizol (ThermoFisher). Similar CL316,243 treatments in mice have been performed in the lab (Ceddia et al, 2021; Liu et al, 2016b).…”
Section: Methodsmentioning
confidence: 73%
“…Based on their biological features, PDE1B and PDE2A are unlikely to contribute to establishing the basal cGMP concentration under resting conditions. Pde5a- knockout mice exhibit small body sizes (Data ref: International Mouse Phenotyping Consortium MGI: 2651499, 2011), and Pde9a -knockout mice have normal body sizes (Ceddia et al , 2021), suggesting that inhibitors of PDE5A and PDE9A are unlikely to stimulate bone growth. Pde6g -knockout mice develop retinitis pigmentosa blindness but have normal body sizes (Tsang et al , 1996).…”
Section: Resultsmentioning
confidence: 99%